Low-cost planar vibration sensor using a modified computer mouse. Issue 4 (15th July 2019) - Xia, Wei; Kong, Lingwen; Zhang, Jiahuan; Hao, Hui; Wang, Yiping; Ni, Xiaoqi; Wang, Ming; Guo, Dongmei
Abstract : Purpose: The purpose of this study aims to modify a self-mixing laser mouse as an extremely cost-effective displacement sensor to measure the mechanical oscillation of a commercial shaker and a nano-positioning stage. Design/methodology/approach: This kind of laser mouse, mostly consisting of a pair of vertical cavity surface emitting lasers, two photodiodes and an integrated signal processing unit, is capable of directly giving the x -axis and y -axis components of the measured vibrating displacement. Based on the laser self-mixing interference, the velocity of the object is coded into the Doppler frequency shift of the feedback light, which allows accurate determination of the vibration of the object. Findings: A commercial shaker has been used to provide standard harmonic oscillation to test the displacement sensor. Within a vibrating frequency range of 110 Hz, the experimental results show that the micrometer scale resolution has been achieved at the velocity of up to 2 m/s, which is much improved compared with the image-based optical mouse. Furthermore, the measurements of the two dimensional displacement of a nano-positioning stage are performed as well. The minimum measurable velocity limit for this sensor has been discussed in detail, and the relative measurement error can be greatly reduced by appropriate selection of the modulation frequency of the triangular injection current. Originality/value: These results demonstrate the feasibility of this device for the industrial vibration sensing applications.